Evaluating the Health Opportunity Costs of COVID-19 Pandemic Prevention, Preparedness, and Response Investment: A Comparative Analysis With Primary Healthcare System Strengthening - Jiao, Meixi (Scientific Journal of Technology, 2026)
This study evaluates the health opportunity costs associated with the allocation of global health resources toward pandemic prevention, preparedness, and response (PPPR) for COVID-19 compared to alternative investments in primary healthcare system strengthening. A central tension in global health policy involves the allocation of finite resources between vertical programs targeting specific diseases and horizontal investments that strengthen foundational health systems. This research addresses this critical resource allocation question by quantifying the health gains derived from $15.25 billion invested through the International Finance Facility for Immunization (IFFIm) and the COVAX Advance Market Commitment (AMC) for COVID-19 vaccine procurement during 2020-2024. Using disability-adjusted life years (DALYs) as the primary outcome measure, the study constructed a counterfactual scenario in which identical resources were allocated to the World Bank's Essential Universal Health Coverage (EUHC) package for low-income countries. Under benchmark assumptions employing a median vaccine price of $13.17 per dose and a number needed to vaccinate (NNV) of 1,000, the factual PPPR investment yielded 22.1 million DALYs averted, while the counterfactual primary healthcare investment would have averted 16.01 million DALYs. The resulting opportunity cost of -6.09 million DALYs indicates that PPPR investment outperformed the alternative scenario. Sensitivity analyses confirmed the robustness of this finding across most parameter variations, with positive opportunity costs emerging only under highly optimistic assumptions regarding primary healthcare delivery efficiency. These findings suggest that emergency pandemic vaccine procurement represented a cost-effective resource allocation strategy from a population health perspective, though sustained investment in primary healthcare remains essential for long-term health system resilience.